2016
DOI: 10.3390/ijms17081306
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunological Implications of AQP4 in Astrocytes

Abstract: The brain has high-order functions and is composed of several kinds of cells, such as neurons and glial cells. It is becoming clear that many kinds of neurodegenerative diseases are more-or-less influenced by astrocytes, which are a type of glial cell. Aquaporin-4 (AQP4), a membrane-bound protein that regulates water permeability is a member of the aquaporin family of water channel proteins that is expressed in the endfeet of astrocytes in the central nervous system (CNS). Recently, AQP4 has been shown to func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 120 publications
4
82
0
2
Order By: Relevance
“…Deletion of the AQP4 gene suppresses the clearance of soluble amyloid β [1]. As a consequence of the regulation of astrocyte membrane water permeability, AQP4 is involved in the rapid volume regulation of astrocytes [13]. Although most studies were performed in vitro , some studies showed astrocyte volume change in vivo using 2-photon microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the AQP4 gene suppresses the clearance of soluble amyloid β [1]. As a consequence of the regulation of astrocyte membrane water permeability, AQP4 is involved in the rapid volume regulation of astrocytes [13]. Although most studies were performed in vitro , some studies showed astrocyte volume change in vivo using 2-photon microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…astrocytes, a major component of the neural network, are increasingly being recognized for their importance in neuroimmunity, including responsiveness to il-1 (6), removal of old cells and secretion of tnf-α/il- 6 (7,8). impaired astrocytic function is regarded as a critical issue implicated in neuroinflammation (9); however, the underlying molecular mechanism remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…it has been well documented that aQP4 is intimately involved in the modulation of astrocyte function (12), but the majority of knowledge on the transporter is limited to water balance (13), glial scar formation (14) and neuroexcitation (15). little focus has been placed on the area of neuroinflammation until recently (9). as found by manley et al (16), aQP4 deletion attenuates AQP4-knockout alleviates the lipopolysaccharide-induced inflammatory response in astrocytes via SPHK1/MAPK/AKT signaling inflammation-related brain edema, providing a novel perspective on aQP4 in the management of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaporin-4 (AQP4) is a water channel protein that can reconcile the homeostasis of water in the BBB. 16,17 Neuro-inammation is a hallmark that induces alterations in brain structure and function in major depressive disorders.…”
Section: Introductionmentioning
confidence: 99%